Pengaruh Harga Minyak Dunia, Inflasi, Pertumbuhan Ekonomi terhadap Pengangguran di Indonesia - Silvia Sefrefita Ayu Dinata; Idris Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2021)
This study describes the Effect of World Oil Prices, Inflation and Economic Growth in Indonesia. This study uses time series data from 1978-2019, with multiple linear regression analysis method. Data sources are from the Central Statistics Agency, BP Statistical, Indonesia Bank and World Bank. The result of the study explain that (1) World Oil Prices have a positive and significant effect on unemployment in Indonesia (2) Inflation has a negative and insignificant effect on unemployment in Indonesia (3) Economic Growth has a negative and insignificant effect on unemployment in Indonesia.